The effects of fermented wheat powder (Lisosan G) on the blood lipids and oxidative status of healthy rabbits. (October 2015) - Pozzo, Luisa; Vizzarri, Francesco; Ciardi, Marco; Nardoia, Maria; Palazzo, Marisa; Casamassima, Donato; Longo, Vincenzo
Abstract: A number of studies have shown that whole grain products have strong antioxidant effects. Lisosan G, a powder produced from the fermentation of Triticum aestivum, has shown hepatoprotective effects. The aim of this paper was to evaluate the effects of Lisosan G on the serum lipid profile and oxidative status of healthy rabbits. Forty rabbits were fed either a normal diet or a diet containing 10 g, 20 g or 30 g Lisosan G/kg of feed for 60 days. The supplementation of Lisosan G did not cause any alteration of the aspartate aminotransferase (AST), alanine aminotransferase (ALT), bilirubin or creatinine concentrations, but caused a reduction in triglycerides, in low density lipoprotein (LDL) cholesterol, and an increase in high density lipoprotein (HDL) cholesterol. The antioxidant activity of Lisosan G has been confirmed on the basis of the reduction in the blood reactive oxygen metabolites (ROMs) and in the level of the thiobarbituric acid reactive substances (TBARS) together with increased vitamin A and E concentrations in the blood. Moreover, Lisosan G also caused the induction of antioxidant enzymes in the liver and kidney of the treated rabbits. This study has shown the ability of Lisosan G to improve the lipid profile and antioxidant status of the blood in healthy rabbits. Highlights: Lisosan G is a powder produced by fermentation of Triticum sativum . Lisosan G improved the plasma triglycerides, total cholesterol, LDL and HDL levels. Lisosan G reduced oxidative stress and increased blood vitamin A and E levels. Lisosan G induced the activity of antioxidant enzymes in liver and kidney. Lisosan G showed a positive effect on blood CVD biomarkers in rabbits.